Domestication and the Epimeletic Character of Man - Marchesini, Roberto (Journal of Ecohumanism, 2024)
The epimeletic theory presented in this article intends to establish man’s disposition towards the adoption of other species and the pleasure and gratification he receives from his relationship with the adopted animal. This theory is founded upon the hypothesis that man is strongly motivated towards parental caring and nurturing behaviour and that this can be explained by means of reference to certain characteristics possessed by human neonates, namely: 1) a very evident physical immaturity at birth, 2) a relatively late age of development, 3) membership of a complex social system. These characteristics not only demand greater and more articulated epimeletic motivation - propensity to give parental care - on the part of our species but consequently make man particularly sensitive and receptive to et-epimeletic signals - baby schema - generally and not exclusively with reference to his own young, thus encouraging the adoption of other species. Epimeletic theory aims to offer an explanation of three phenomenona: a) the domestication of animals by man, b) the relationship established through pet ownership, c) the beneficial nature of activities connected with the man-pet relationship (pet therapy, pet education).